1918
DOI: 10.1001/jama.1918.26020500021006h
|View full text |Cite
|
Sign up to set email alerts
|

Relapses After Apparent Recovery in Delayed Tetanus

Abstract: inrush of air. It is advisable to use very little pressure in irrigating lest the lung be torn loose from its newly formed adhesions to the chest wall. For the same reason, also, the patient should be protected from coughing during the first five days of the drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a review of the human literature, the first recurring case was reported by Whittemore et al. in 1918 and this has been followed by other isolated single cases (Lemere et al., 1941; Vakil et al., 1964; Spenney et al., 1971; Bhatt et al., 1981; Lindley‐Jones et al., 2004; Wakasaya et al., 2009 and Alhaji et al., 2011). In addition, three case series are described in the human literature (Garcia‐Palmieri & Ramirez, 1957 reported on 5 cases; Patel et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a review of the human literature, the first recurring case was reported by Whittemore et al. in 1918 and this has been followed by other isolated single cases (Lemere et al., 1941; Vakil et al., 1964; Spenney et al., 1971; Bhatt et al., 1981; Lindley‐Jones et al., 2004; Wakasaya et al., 2009 and Alhaji et al., 2011). In addition, three case series are described in the human literature (Garcia‐Palmieri & Ramirez, 1957 reported on 5 cases; Patel et al.…”
Section: Discussionmentioning
confidence: 98%
“…Little or no active immunity develops as a result of clinical tetanus in people (Turner et al, 1957;Vakil et al, 1964), yet despite this, reports of relapsing or recurrent tetanus in people are very rare and non-existent amongst equids. In a review of the human literature, the first recurring case was reported by Whittemore et al in 1918 and this has been followed by other isolated single cases (Lemere et al, 1941;Vakil et al, 1964;Spenney et al, 1971;Bhatt et al, 1981;Lindley-Jones et al, 2004;Wakasaya et al, 2009 andAlhaji et al, 2011). In addition, three case series are described in the human literature (Garcia-Palmieri & Ramirez, 1957 reported on 5 cases; Patel et al 1961 on 17 cases andVakil et al, 1964 on 11 cases).…”
Section: Discussionmentioning
confidence: 98%